Problematizing a ‘fundamentalist’ ideology: A close analysis of Atef Hetata’s The Closed Doors and Phil Mullaly’s The Martyrs of Uganda - Mushengyezi, Aaron (Journal of African cinemas, 2009)
This paper discusses Atef Hetata’s The Closed Doors and Phil Mullaly’s The Martyrs of Uganda and the ways in which they problematize a “fundamentalist” vision. Through close reading and analysis of the language, cinematographic and mise en scène elements in these films, the paper examines the cineastes’ portrayal of the dilemmas and dangers posed when extremist religious dogma conflicts with the socio-economic and political realities and contradictions in society. The paper raises questions about the course of action human beings choose in pursuit of extremist agendas today in a world where tolerance for diversity and multiculturalism has become part and parcel of a new global culture.